Effectiveness of “ Si Bumil Application ” in Reducing Anxiety of Pregnant Women in the Thirty-Trimester - Silvi Zaimy; Meldafia Idaman; Herman Susilo (GLOBAL HEALTH SCIENCE GROUP, 2025)
Anxiety on time pregnancy impact negative to labor, health mentally Mother postpartum, And health baby Provision of web-based facilities via mobile phones and the internet can help reduce anxiety and stress in pregnant women. The “Si Bumil application” is expected to be a health education medium for pregnant women in reducing the anxiety they experience. The purpose of this study was to determine the effectiveness of the Si Bumil application in reducing anxiety in pregnant women in the third trimester. Method: A pretest-posttest control group approach was used in this quasi-experimental investigation. At PMB Padang City, 44 pregnant women in their third trimester participated in the study. The sampling technique was accidental sampling . The sample was divided into two groups, namely the intervention group with educational provision using the Si Bumil application and the control group with educational provision using power point media. Pregnant women's anxiety was assessed using the Hamilton Anxiety Scale (HARS) questionnaire. Statistical test using Independent t-test. According to the findings, for pregnant women in the intervention group, the average score of anxiety was 27.40 ± 3.17, whereas for those in the control group, the average score was 26.36 ± 2.85. After the intervention, the average score of anxiety of pregnant women in the intervention group was 19.13 ± 3.97 and in the control group 24.86 ± 2.62. The average score of anxiety of pregnancy after the intervention was compared between the intervention group and the control group, it was found that the level of anxiety experienced by pregnant women in both groups had decreased. However, the level of anxiety experienced by pregnant women in the intervention group showed a bigger drop than the control group. The results of the test of the difference in stress scores of the two groups showed that there was a significant difference (p = 0.000. This study indicated that coordinating Web-based education is an effective technique for reducing anxiety among pregnant women. As a result, it is advised that this Web-based method